Measuring and Analyzing The Impact of Public Spending on Economic Stability in Iraq For The Period 2010-2024 - Mustafa Ibrahim Abdullah; Wasan Mashal Sarhan; Abdullah Muhammad Rashid Al-Ramli (Journal of Economics, Assets, and Evaluation, 2026)
This study aims to measure and analyze the impact of public spending on achieving economic stability in Iraq during the period 2010–2024, in light of the structural fluctuations experienced by the Iraqi economy resulting from oil shocks and political and health crises The study adopted a quantitative approach based on time series data for public spending and the economic stability indicator (GDP). Econometric models, such as the Autoregressive Lag Diagram (ARDL), were also used to analyze the long-term and short-term relationships between the variables. Preliminary findings indicate that public spending in Iraq tends to be expansionary, with a significant concentration on current expenditures compared to investment spending, thus limiting its capacity to generate sustainable growth. The results also showed a significant relationship between public spending and short-term economic stability indicators, but no such relationship was found in the long term. Furthermore, the findings suggest that the Iraqi economy is highly sensitive to fluctuations in oil revenues, making the impact of public spending on stability contingent on the ability of fiscal policy to manage the economic cycle and achieve a balance between spending and revenues